Interatheriidae (Typotheria; Notoungulata), body size and paleoecology characterization - Scarano, Alejo Carlos (2011)
Size has a major influence on animal’s adaptation to its environment and is central to paleobiological characterization of fossil mammals. We present new models of body mass estimation for the Interatheriidae (Notoungulata, Typotheria). This small herbivorous mammals extends from the late Paleocene to the late Miocene and they are very well represented in the paleontological record of southern South America during a geological time lapse that witnessed extremely important events, at both climatic and biotic levels. The importance of the group as paleoecological indicators for a great part of the Cenozoic is emphasized by their long biochron and abundance in the fossil record. In this context, estimation of the body mass becomes crucial to reconstruct and infer ecologicalenvironmental structure for a given time period. The results of the calculation of body masses from these new equations shows overall narrower range, smaller deviations, lower de-transformation correction and lower prediction error than previous equations used for body mass estimation in herbivores ungulates, establishing the maximum body mass for the Interatheriidae in 8.3 kg. These new body masses were utilized for characterization of the nutritional ecology of Protypotherium australe (early Miocene), suggesting browser habits but it does not exclude grass from been part of the diet.